2009
DOI: 10.1074/jbc.r109.025544
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-6-phosphatase Catalytic Subunit Gene Family

Abstract: Glucose-6-phosphatase catalyzes the hydrolysis of glucose 6-phosphate (G6P) to glucose and inorganic phosphate. It is a multicomponent system located in the endoplasmic reticulum that comprises several integral membrane proteins, namely a catalytic subunit (G6PC) and transporters for G6P, inorganic phosphate, and glucose. The G6PC gene family contains three members, designated G6PC, G6PC2, and G6PC3. The tissuespecific expression patterns of these genes differ, and mutations in all three genes have been linked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
140
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(144 citation statements)
references
References 52 publications
3
140
0
1
Order By: Relevance
“…Как и в случае с ФЕП-карбоксикиназой, регуляция активности глюкозо-6-фосфатазы осущест-вляется не посттрансляционно, а посредством измене-ния уровня ее экспрессии. Промотор гена этого фермента несет многочисленные участки связывания с гормончув-ствительными транскрипционными факторами и коакти-ваторами [12] (рис. 1) Регуляция глюконеогенеза может осуществляться двумя путями: посттрансляционно и претрансляционно.…”
Section: глюконеогенезunclassified
“…Как и в случае с ФЕП-карбоксикиназой, регуляция активности глюкозо-6-фосфатазы осущест-вляется не посттрансляционно, а посредством измене-ния уровня ее экспрессии. Промотор гена этого фермента несет многочисленные участки связывания с гормончув-ствительными транскрипционными факторами и коакти-ваторами [12] (рис. 1) Регуляция глюконеогенеза может осуществляться двумя путями: посттрансляционно и претрансляционно.…”
Section: глюконеогенезunclassified
“…In accord with this, it has been reported that HNF4α plays a critical role in fatty acid-induced DISCUSSION Gluconeogenesis is determined primarily by G6Pase and PEPCK, two major enzymes involved in the rate limiting steps of this pathway. As G6Pase, as well as PEPCK, regulates gluconeogenesis at the levels of transcription, the molecular mechanism of G6pc transcription has been studied extensively (9,10,19,24). G6pc transcription is known to be modulated by nutrients, metabolites, and hormones (8,11,13,18).…”
Section: Temporal Changes Of G6pc Expression By Glycerol And/or Oleatementioning
confidence: 99%
“…However, the current mutational spectrum in a limited number of patients has not yet allowed a clear genotypephenotype correlation [160 && ]. G6PC3 is a ubiquitously expressed metabolic enzyme of the glucose 6 phosphatase (G6P) family, that is G6PC1-3, which localizes to the endoplasmic reticulum membrane where it is supposed to form a functional complex with glucose-6-phosphate transporter (G6PT), also known as solute carrier family 37 member 4 (SLC37A4) [161,162]. Neutrophil granulocyte G6PC3 deficiency deranges glucose recycling between the endoplasmic reticulum and the cytoplasm and leads to reduced levels of glucose uptake and its energy-carrying catabolites obtained by glycolysis [163].…”
Section: G6pc3 Deficiency (Scn4)mentioning
confidence: 99%